The effects of probiotic bacteria on glycaemic control in overweight men and women: a randomised controlled trial - Ivey, K.; Hodgson, J.; Kerr, Deborah; Lewis, J.; Thompson, P.; Prince, R. (Nature Publishing Group, 2014)
Background/Objectives: Evidence from animal and in vitro models suggest a role of probiotic bacteria in improving glycaemic control and delaying the onset of type 2 diabetes. However, the evidence from controlled trials in humans is limited. The objective was to determine if the probiotic bacteria L. acidophilus La5 and B. animalis subsp lactis Bb12, supplemented in a whole food (yoghurt) or isolated (capsules) form, can improve biomarkers of glycaemic control. Subjects/methods: Following a 3-week washout period, 156 overweight men and women over 55 years (mean age: 67±8 years; mean body mass index (31±4 kg/m2) were randomized to a 6-week double-blinded parallel study. The four intervention groups were: (A) probiotic yoghurt plus probiotic capsules; (B) probiotic yoghurt plus placebo capsules; (C) control milk plus probiotic capsules; and (D) control milk plus placebo capsules. Outcome measurements, including fasting glucose, insulin, glycated haemoglobin and Homoeostasis Model Assessment of Insulin Resistance (HOMA-IR), were performed at baseline and week 6. Results: Relative to the milk-control group, probiotic yoghurt resulted in a significantly higher HOMA-IR (0.32±0.15, P=0.038), but did not have a significant effect on the other three measures of glycaemic control (P>0.05). Relative to placebo capsules, probiotic capsules resulted in a significantly higher fasting glucose (0.15±0.07 mmol/l, P=0.037), with no significant effect on the other three measures of glycaemic control (P>0.05). Further analyses did not identify other variables as contributing to these adverse findings. Conclusions: Data from this study does not support the hypothesis that L. acidophilus La5 and B. animalis subsp lactis Bb12, either in isolated form or as part of a whole food, benefit short-term glycaemic control. Indeed, there is weak data for an adverse effect of these strains on glucose homoeostasis.